Pengaruh Kelelahan Terhadap Produktivitas Kerja pada Petugas Incoming Cargo (PT. Persero Batam) di Bandar Udara Internasional Hang Nadim Batam - Abi Bayu Saputra; Yunus Purnama (QISTINA: Jurnal Multidisiplin Indonesia, 2026)
The aviation industry, particulary the cargo sector, has experienced significant growth in the wake of the COVID-19 pandemic, marked by an increase in the volume of domestic air cargo transportation. This has a direct impact on operational activites at airport cargo terminals, especially for incoming cargo officers who are responsible for receiving, processing, documents, and distributing goods. Routine, repetitive work activites that require a high degree of accuracy have the potential to cause physical and mental fatigue, which can reduce the productivity of officers. This study aims to analyze the effect of fatigue on the work productivity of incoming cargo officers at PT. Persero Batam at Hang Nadim Intenational Airport in Batam and the magnitude of this effect. This study uses a quantitative approach with simple linear regression analysis. The population consists of 51 incoming cargo officers, using total sampling technique. However, one extreme data point was excluded, resulting in a final sampel of 50 respondents. Primary data was obtained through questionnaires, while secondary data was obtained from literature relevant to this study. The analysis was conducted using SPSS Version 25, including classical assumption test, partial t-test, and determination coefficients. The result of this study indicate that fatigue has a significant effect on the work productivity of incoming cargo officers, with a significance value of 0,000 < 0,05 and t-count of 21,622 > t-table 1,677. The R Square value of 0,907 indicates that fatigue contributes 90,7% to work productivity, while the remaining 9,3% is influenced by other factors outside the scope of this study.